Immersive Nature-Experiences as Health Promotion Interventions for Healthy, Vulnerable, and Sick Populations? A Systematic Review and Appraisal of Controlled Studies - Mygind, Lærke; Kjeldsted, Eva; Hartmeyer, Rikke Dalgaard; Mygind, Erik; Bølling, Mads; Bentsen, Peter (Frontiers in Psychology, 2019)
In this systematic review, we summarized and evaluated the evidence for effects of, and associations between, immersive nature-experience on mental, physical and social health promotion outcomes. Immersive nature-experience was operationalized as non-competitive activities, both sedentary and active, occurring in natural environments removed from everyday environments. We defined health according to the World Health Organization’s holistic and positive definition of health and included steady-state, intermediate, and health promotion outcomes. An electronic search was performed for Danish, English, German, Norwegian, and Swedish articles published between January 2004 and May 2017. Manual approaches, e.g., bibliographies from experts, supplemented the literature search. Data were extracted from 461 publications that met the inclusion criteria. To assess the status and quality of the evidence for health promotion effects of immersive nature-experience, we focused on the subset of studies based on controlled designs (n = 133). Outcome level quality of the evidence was assessed narratively. Interventions most often involved adventure-based activities, short-termed walking, and seated relaxation in natural environments. We found positive effects on a range of health promotion outcomes grouped under psychological wellbeing (n = 97; ≈55% positive; ≈13% mixed; ≈29% non-significant; 2% negative); psychosocial function (n = 67; ≈61% positive; ≈9% mixed; ≈30% non-significant); psychophysiological stress response (n = 50; ≈58% positive; ≈18% mixed; ≈24% non-significant), and cognitive performance (n = 36; ≈58% positive; ≈6% mixed; ≈33% non-significant; 3% negative); and social skills and relationships (n = 34; ≈70% positive; ≈7% mixed; ≈22% non-significant). Findings related to outcomes categorized under physical health, e.g., risk of cardiovascular disease, were less consistent (n = 51; ≈37% positive; ≈28% mixed; ≈35% non-significant). Across the types of interventions and outcomes, the quality of the evidence was deemed low and occasionally moderate. In the review, we identify, discuss, and present possible solutions to four core methodological challenges associated with investigating immersive nature-experience and health outcomes: 1) intervention and program complexity; 2) feasibility and desirability of randomization; 3) blinding of participants and researchers; and 4) transferability and generalizability. The results of the review have been published as a popular-scientific report and a scientific research overview, both in Danish language.